Association of the interaction between nutritional status and frailty level with sleep quality in older adults - Yang, Shaoting; Zhang, Yumeng; Jiang, Zhixia; Liang, Heting; Mao, Qingyun; Wen, Honghong; Xiong, Yan; Li, Yunting; Yuan, Xiaoli (Frontiers in Public Health, 2025)
BackgroundSleep quality decline is common among older adults, affecting their physical and mental health and reducing quality of life. Research shows a notable link between older adults’ nutritional status, frailty, and sleep quality.ObjectiveThis study delves into the interaction between older adults’ nutritional status and frailty on sleep quality, aiming to offer scientific strategies for improving sleep.MethodsVia convenience sampling, a one-year cross-sectional survey was conducted on 14,021 seniors aged 60+ from 7 medical facilities, 3 communities, and 5 nursing homes in Zunyi, Guizhou. The survey covered general data, FRAIL Scale, MNA-SF, and PSQI. Logistic regression explored relationships, and a generalized linear model evaluated interactions.ResultsOf the 14,021 older adults, 24.3% had poor sleep. Factors like gender, age, education, residence, income, habits, social engagement, physicals, exercise, and support was significantly associated with sleep quality (all p < 0.05). Logistic regression affirmed nutritional status (OR = 1.076–1.193) and frailty (OR = 3.472–6.050). After controlling variables, generalized linear model showed nutritional status (B = 0.007), frailty (B = 1.145), and their interaction (B = 0.214), being significant (p < 0.05).ConclusionMalnutrition and frailty synergistically exacerbate sleep disturbances in older adults. Integrated interventions targeting nutritional support and frailty mitigation are critical to improving sleep health in this vulnerable population.